Somatic Embryogenesis and Plant Regeneration from Cell Suspension Culture of Gymnema sylvestre (Retz) R. Br. Ex Roemer & Schultes - Ali Ahmed*, Abdul Bakrudeen; Suryanarayana Rao, Adhikarla; Venkateswara Rao, Mandali (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
We have optimized a system for the somatic embryogenesis via embryogenic suspension cultures of Gymnema sylvestre. Callus cultures were induced on MS medium with growth regulators (2,4 -D 0.5 mg/l (or) NAA 1.0 mg/l) and 10% coconut water. They were transferred into MS liquid medium containing NAA 1.0 mg/l, BA 1.0 mg/l, 3.0% sucrose (w/v), 10% coconut water, citric acid 1 mg/l and glutamine 10 mg/l for somatic embryogenesis from callus. Globular, heart, torpedo and cotyledonary stage of embryos were observed in suspension cultures after 8 weeks. The maturation embryos were significantly affected by growth regulators and photoperiod. Five to seven percent of embryos formed plantlets on semisolid medium containing basal MS medium with B5 vitamin, 3.0% sucrose and 0.8% agar (w/v). All plantlets established in the field exhibited morphological characters similar to those of the mother plant. Keywords: Gymnema sylvestre; MS medium; embryogenic callus; cell suspension culture; somatic embryos; plant growth regulators. * Corresponding author: E-mail: dr.bakrudeenaliahmed@yahoo.co.in